Dietary inulin supplementation improves meat quality and off-flavor of duck meat referring to regulated muscle fiber types and antioxidant capacity - Hailei Sun; Jia Wang; Jina Han; Xiaolong Li; Juan Zhao; Yimin Zhang; Jingxin Sun (Food Chemistry: X)
This study aimed to evaluate the effects of dietary inulin (0–30 g/kg) on duck meat, muscle fiber types, meat quality, antioxidant ability, Low-field nuclear magnetic resonance, amino acid and off-flavor. These results indicated that inulin promoted the conversion of type II to type I muscle fibers. Compared with the control group, supplementation with 20 g/kg inulin reduced (P < 0.05) the shear force and pressure water loss by 17.9 N and 1.9 %, respectively. Inulin increased the pH24h and the redness of duck meat. Low-field nuclear magnetic resonance confirmed that inulin increased the immobile water content and enhanced water retention in duck meat. Additionally, inulin enhanced antioxidant capacity and reduced the degree of lipid oxidation. Inulin increased the content of umami and sweet amino acids by 2.63 %, which affects the flavor of duck meat. Notably, dietary inulin reduced the content of volatile off-flavor substances and improved the flavor of duck meat. In summary, dietary inulin may be an effective strategy for producing high quality duck meat and removing duck off-flavor.